Comparison of intrathecal morphine versus local infiltration analgesia for pain control in total knee and hip arthroplasty: A meta-analysis. Issue 36 (4th September 2020) - Qi, Bao-chang; Yu, Jing; Qiao, Wei-song
Abstract: Background: The purpose of this meta-analysis was to comprehensively collect randomized controlled trials (RCTs) to assess the clinical efficacy of intrathecal morphine (ITM) versus local infiltration analgesia (LIA) in the treatment of total knee and hip arthroplasty patients. Methods: Relevant studies were identified from the Embase, PubMed, Cochrane Library, Web of Science, Wanfang, and Chinese National Knowledge Infrastructure (CNKI) databases. We also reviewed the references of all identified articles to identify additional studies. For each study, we assessed the risk ratio (RR), weighted mean difference (WMD), and corresponding 95% confidence interval (95% CI) to synthesize outcomes. Meta-analysis was performed with Stata 12.0 software. Results: We included 13 studies with 942 patients for meta-analysis. LIA significantly decreased the pain value with rest or mobilization until 72 hours ( P < .05). LIA significantly decreased cumulative morphine consumption by 13.52 mg. Moreover, the length of hospital stay was lower in the LIA group than in the ITM analgesia group. Finally, LIA significantly reduced morphine-related complications (nausea and vomiting, pruritus, and respiration depression). Conclusions: LIA was an effective approach for relieving postoperative pain and reducing postoperative consumption of morphine compared with ITM in total knee and hip arthroplasty patients.